ІНТЕРПРЕТАЦІЙНІ УСТАНОВКИ ФОРТЕПІАННИХ ПРЕЛЮДІЙ Б. ЛЯТОИІИНСЬКОГОУ МУЗИЧНО-ПЕДАГОГІЧНІЙ ПІДГОТОВЦІ СТУДЕНТА (Педагогіка вищої та середньої школи, 2007)
The article deals with possibilities of interpretive outputs to concert-performance and pedagogic activity under conditions of music and pedagogic training of students based on piano prelusions by B. Lyatoshinsky. A stylistic factors analysis of the composer’s prelusions piano cycles is of special attention as the basis for personal interpretation «strategies» formation.